Analisis Kepentingan Umum Dalam Asas Oportunitas Pada Sistem Peradilan Pidana - Iqbal, Muhammad; Ilham, Muhammad Azham (Qawanin Jurnal Ilmu Hukum, 2022)
This research aims to examine and analyze the development and criteria of public interest in the principle of opportunity in the criminal justice system. The research uses normative legal methods by using statutory approaches, legal theories and opinions of legal experts with secondary, primary and tertiary legal materials. With this research the author obtains answers to the existing problems that the existence of the prosecutor as an institution that has the authority to set aside cases based on public interest to avoid abuse of authority and ensure legal certainty in order to apply the principle of opportunity based on public interest in the criminal justice system, the Attorney General sets aside in a letter of determination or provides a copy of the decision to set aside the case for the evidence concerned, that the case is set aside in accordance with the rules in the legislation After the revocation of Law No. 5 of 1961 replaced by Law No.5 of 1991 concerning the Attorney General of the Republic of Indonesia. 1991 concerning the Prosecutor's Office of the Republic of Indonesia, the setting aside of cases based on public interest in the principle of opportunity in the criminal justice system is still maintained in Article 32 letter c which clearly says: "The Attorney General may file cases based on public interest". Translated with DeepL.com (free version). differences in the application of the principle of opportunity in the criminal justice system in Law Number 5 of 1991 "The interests of the Nation and the wider community." Prior to this provision in Indonesia, in practice, the principle of opportunity had been adopted which was commonly considered as unwritten law. in the development of the principle of opportunity, it has undergone many changes from time to time and the criteria for public interest in the principle of opportunity as the interests of the State, the interests of society and for the sake of personal interests. This interpretation has not provided a concrete interpretation and measure so that it can provide different interpretations. the vagueness of this rule suggests that the rules contained in a law should be in its formation to consolidate with related parties who understand in depth about the principle of opportunity. Abstrak: Penelitian ini bertujuan untuk mengkaji dan menganalisis perkembangan dan kreteria kepengtingan umum dalam asas oportunitas pada sisitim peradilan pidana. Penelitian menggunakan metode hukum normatif dengan menggunakan pendekatan perundang-undangan, Teori Hukum serta pendapat para ahli hukum dengan bahan hukum sekunder, primer dan tersier. dengan penelitian ini penulis memperoleh jawaban dari permasalahan yang ada bahwa Keberadaan jaksa sebagai lembaga yang memiliki kewenangan untuk mengesampingkang perkara berdasarkan kepengtingan umum untuk menghindarkan penyalagunaan wewenang dan terjaminnya kepastiang hukum dalam rangka menerapkan asas oportunitas berdasarkan kepengtingan umum pada sisitim peradilan pidana, Jaksa Agung menuangkang dalam surat penetapan atau memberikan salinan keputusan dikesampingkannya perkara tersebut untuk sebagai bukti yang bersangkutan, Bahwa perkara tersebut dikesampingkan suda sesuai dengan aturan dalam perundang-undangan Setelah dicabutnya Undang-Undang Nomor 5 Tahun 1961 diganti dengan Undang-Undang No.5 Tahun 1991 tentang Kejaksaan Republik Indoesia pengsamping perkara berdasarkan kepengtingan umum dalam asas oportunitas pada sisitim perdilan pidana tetap dipertahangkan dalam Pasal 32 huruf c yang secara jelas dikataan: “Jaksa Agung dapat menyampigkan perkara berdasarkan kepentingan umum” perbedaan dalam penerapan asas oportunitas dalam sisitim peradilan pidana pada Undang-Undang Nomor 5 Tahun 1991 “Kepengtingan Bangsa dan Masyrakata luas.” Sebelum ada ketentuan tersebut di Indonesia dalam praktek telah dianut asas oportunitas yang lazim dianggap sebagai hukum tidak tertulis. dalam perkembangan asas oportunitas telah banyak mengalami perubahan dari masa kemasa dan Kreteria kepengtingan umum dalam asas oportunitas sebagai Kepentingan Negara, kepentingan masyarakat dan Demi kepentingan pribadi. penafsiran ini belum memberikan pengjalsan dan ukuran yang konkrit sehingga dapat memberikan penafsiran yang berbeda-beda. ketidak jelasan aturan ini menyarankan agar aturan yang dimuat dalam sebua Undang-Undang kiranya dalam pembentukannya untuk mengkonsilidasikan dengan pihak yang terkait yang memahami secara mendalam tentang asas oportunitas.